Estratégia-como-prática na Economia Solidária. Resultados e Ações de Catadores de uma Cooperativa - Maria de Lourdes Borges (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2015)
AbstractThis aim is analyze the manifestation of the dynamics within organizational processes in “strategy-as--practice” starting from results and actions collectors of recyclable material’s “Cooperativa de TrabalhoAmigas e Amigos Solidário (Cooarlas)” in Canoas / RS, Brazil. Then, the methodology employed isthe case study. The results show the strategic change in its path engendered by organizational actors(coordination and coop) that led to favorable results. The article pointed out that advances the studyof strategy as practice in the context of the solidarity economy can light on the gap of studies takeplace in a ‘organizational vacuum’ through reciprocity and solidarity logics; evidence of cooperativeaction as real social actors of strategy-as-practice; benefits of the strategy-as-practice study in thecontext of the solidarity economy, solidarity, culture of cooperation and building a habitus of coope-rative work can be observed.